Choice of biomaterials—Do soft occlusal splints influence jaw-muscle activity during sleep? A preliminary report - Arima, Taro; Takeuchi, Tamiyo; Tomonaga, Akio; Yachida, Wataru; Ohata, Noboru; Svensson, Peter (Applied surface science, 2012)
► Tested if choice of biomaterials for occlusal splints influences biological outcome such as jaw-muscle activity during sleep. ► Jaw-muscle activity during sleep was decreased by wearing hard-material occlusal splint. ► Jaw-muscle activity during sleep was not influenced by wearing soft-material occlusal splint. ► This specific choice of biomaterials may have impact on the neurobiological regulation of jaw-muscle activity during sleep. The choice of biomaterials for occlusal splints may significantly influence biological outcome. In dentistry, hard acrylic occlusal splints (OS) have been shown to have a temporary and inhibitory effect on jaw-muscle activity, such as tooth clenching and grinding during sleep, i.e., sleep bruxism (SB). Traditionally, this inhibitory effect has been explained by changes in the intraoral condition rather than the specific effects of changes in occlusion. The aim of this preliminary study was to investigate the effect of another type of occlusal surface, such as a soft-material OS in addition to a hard-type OS in terms of changes in jaw-muscle activity during sleep. Seven healthy subjects (mean±SD, six men and one woman: 28.9±2.7 year old), participated in this study. A soft-material OS (ethylene vinyl acetate copolymer) was fabricated for each subject and the subjects used the OS for five continuous nights. The EMG activity during sleep was compared to baseline (no OS). Furthermore, the EMG activity during the use of a hard-type OS (Michigan-type OS, acrylic resin), and hard-type OS combined with contingent electrical stimulation (CES) was compared to baseline values. Each session was separated by at least two weeks (washout). Jaw-muscle activity during sleep was recorded with single-channel ambulatory devices (GrindCare, MedoTech, Herlev, Denmark) in all sessions for five nights. Jaw-muscle activity during sleep was 46.6±29.8 EMG events/hour at baseline and significantly decreased during the hard-type OS (17.4±10.5, P=0.007) and the hard-type OS+CES (10.8±7.1, P=0.002), but not soft-material OS (36.3±24.5, P=0.055). Interestingly, the soft-material OS (coefficient of variance=98.6±35.3%) was associated with greater night-to-night variations than baseline (39.0±11.8%) and the hard-type OS+CES (53.3±13.7%, P<0.013). The present pilot study in small sample showed that a soft-material occlusal splint does not seem to inhibit jaw-muscle activity during sleep. Within the limitation of the study, it appears that the choice of biomaterials for occlusal splints may have a significant impact on the neurobiological regulation of jaw-muscle activity during sleep.